Konjungsi pada Kanal Youtube Mata Najwa episode “Putusan MK: Publik Memang Seharusnya Marah” - Ramadhan, M. Raihan; Asnawi, Asnawi (Jurnal Bahasa dan Sastra, 2024)
This research investigates the role of conjunctions in constructing cohesive narratives on Najwa Shihab's YouTube channel in the episode “Putusan MK: Publik Memang Seharusnya Marah”. Employing a qualitative discourse analysis approach, data was collected through non-participant observation and analyzed using Moeliono et al.'s (2017) framework for the types and functions of conjunctions. The analysis results demonstrate that both coordinating and subordinating conjunctions remain integral elements in Shihab's narratives. These conjunctions serve various functions, including providing contextual details to enhance explanations, emphasizing Shihab's viewpoints, and presenting perspectives or alternative choices to the viewers. Ultimately, this study highlights how Shihab's strategic use of conjunctions promotes coherence in her narratives, fostering audience engagement and understanding.